1954
DOI: 10.1161/01.cir.10.5.699
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Hereditary Susceptibility in Rheumatic Fever

Abstract: This study is concerned with the pattern of inheritance of susceptibility to rheumatic fever. To investigate the genetic mechanism of inheritance in rheumatic fever the families of a selected parent were brought under observation without regard for the presence or absence of rheumatic fever in the unselected mate or collateral relatives. These data are preferable for genetic analysis since they are not biased by selection of affected children and can therefore be analysed directly by the application of simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1956
1956
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…Again, individual factor is determinant of disease pattern and is poorly understood. Familiar aggregation [9,10], similarity of disease patterns between siblings and identical twin [11] and HLA correlation studies [8] are evidence for a genetic influence on RF susceptibility and manifestation. The suspect-involved genes fall mainly into those capable of immunologic mediation.…”
Section: Introductionmentioning
confidence: 99%
“…Again, individual factor is determinant of disease pattern and is poorly understood. Familiar aggregation [9,10], similarity of disease patterns between siblings and identical twin [11] and HLA correlation studies [8] are evidence for a genetic influence on RF susceptibility and manifestation. The suspect-involved genes fall mainly into those capable of immunologic mediation.…”
Section: Introductionmentioning
confidence: 99%
“…Early but unconfirmed studies suggested that susceptibility to rheumatic fever followed a simple autosomal recessive pattern of inheritance (4)(5)(6), or paralleled the inheritance of ABO blood group or ABO secretor status (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The pathogenesis of rheumatic fever is also thought to involve an aberrant immunological reaction, either humoral or cellular, or both, triggered by an antecedant group A streptococcal infection (18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…D avies and G ery [16] have studied the possibility of patients' serum reaction on antigenic heart tissue in various types of heart diseases and came to the conclusion, that only a limited number of people had ability to form circulating antibody. They expected also that the hereditary factor was of some importance, as W ilson and Schweitzer [17] have described.…”
Section: Discussionmentioning
confidence: 89%